Effects of melittin on isolated papillary muscles of guinea pig - Zhang Ying-Li; Yang Shen; Shi Nian-Ci; Jiang Ming-Hua (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of melittin (Mel) on papillary muscles of guinea pigs. Methods: Contraction of papillary muscles were examined by conventional method and action potentials (AP) were recorded by standard glass microelectrode technique. Results: Mel (0.5, 3 micromol/L) significantly increased the contractility of guinea pig papillary muscles while 5 micromol/L exerted dual action with a transient decrease followed by an increase of the contractility. Mel shortened the functional refractory period (FRP) at concentrations of 0.5, 3, and 5 micromol/L and increased the automaticity induced by adrenaline (Adr) at 3 and 5 micromol/L. Mel shifted the duration-intensity curve upward at 3 micromol/L. It shortened the action potential duration (APD) of fast action potential (FAP), decreased the action potential amplitude (APA) and resting potential (RP) at 0.5 and 3 micromol/L. As to slow action potential (SAP), Mel 0.8 micromol/L shortened APD20 and APD50, and decreased APA and RP. Conclusion: Mel increased the contractility and automaticity of papillary muscles, shortened the FRP, decreased the excitability, shortened the APD, and decreased APA and RP of AP.